Pengelolaan Pembelajaran Geografi Berbasis LaboratoriumDi SMA Negeri 7 Purworejo Tahun 2014 - HARTONO, Ucik (2014)
The purposes of this research are to describe: (1) the planning; (2) the implementation; and (3) the evaluation of Laboratory-Based Geography Learning at SMA Negeri 7 Purworejo. This research is a qualitative research. For the method of collecting data, it uses observation, interview, and documentation. The results of the research show that: (1) Its planning was done by preparing the Laboratory, Lesson Plan, Instructional material, as well as preparing instructional media for geography subject. (2) Laboratory-based Geography learning at SMA Negeri 7 Purworejo was started by praying together, greetings, as well as apperception and motivation. The initial activities also included the introduction of material to be covered, the introduction of laboratory equipment that were deemed to be foreign to the students, and the material points which need to be developed and studied. Core activities were focused on the following activities-observing, analyzing, creating work, and practicing learning tools. The last activities carried out by giving conclusion on the material presented, followed by giving the quiz and praying together. (3) Assessment in Laboratory-based Geography learning was done by written and oral tests. Assessment was also done by assessing students' work, and the skills to use the tools / instructional materials. The assessment of Laboratorybased Geography learning was conducted from the early observation during discussions and presentations. By using a laboratory-based learning, students' interest and motivation were getting higher, so the result was also increased. All students were able to achieve a specified KKM score